Consumer protection on food and environmental safety based on statutory implied terms in Malaysian sale of goods law : focusing on urban sustainability. - Razman, Muhammad Rizal; Azlan, Azrina; Md. Jahi, Jamaluddin; Arifin, Kadir; Aiyub, Kadaruddin; Awang, Azahan; Mohamad, Lukman @ Zawawi (Medwell Online, 2010)
Consumers take part in essential role in contributing to the development of the country’s economy which include urban region as the result there are many conferences, symposiums and seminars which have been organised for the purpose to enhance the awareness on their rights. Therefore, this study will discuss on how the Malaysian statutory implied terms in the sale of goods law provide protection to consumer protection on food and environmental safety focusing on urban sustainability. The core reference of this study is based on Malaysian Sale of Goods Act, 1957.